2017
DOI: 10.1002/cbin.10898
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to mitochondrial research in Brazil: 10th anniversary of the mitomeeting

Abstract: This commentary introduces the subject, the context and the history of the Brazilian annually held meeting on Mitochondrial Research by the occasion of its 10th anniversary. Mitomeetings gather people interested in all aspects of mitochondrial biology in diverse species, including protists, animals, plants, and fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The trends in publications on general mitochondrial metabolism in Brazil and in all South American countries combined are also very similar to that seen worldwide ( Figure 3A , left panel). The contributions of Brazilian mitochondrial researchers to the field in the last 20 years have been substantial and are highlighted elsewhere ( Vercesi and Oliveira, 2018 ). However, analyzing the output of Drosophila mitochondrial metabolism research from Brazil showed that no publication was recorded before 2007 and that an average of less than 3 articles on the subject were published per year since then ( Figure 3A , right panel).…”
Section: Limited Output Of Many Areas Of Drosophila ...mentioning
confidence: 99%
“…The trends in publications on general mitochondrial metabolism in Brazil and in all South American countries combined are also very similar to that seen worldwide ( Figure 3A , left panel). The contributions of Brazilian mitochondrial researchers to the field in the last 20 years have been substantial and are highlighted elsewhere ( Vercesi and Oliveira, 2018 ). However, analyzing the output of Drosophila mitochondrial metabolism research from Brazil showed that no publication was recorded before 2007 and that an average of less than 3 articles on the subject were published per year since then ( Figure 3A , right panel).…”
Section: Limited Output Of Many Areas Of Drosophila ...mentioning
confidence: 99%